Edukasi Berbasis Eksoterik pada Kelompok Dewasa Hipertensi di Kelurahan Curug Kota Depok - Rasdiyanah Rasdiyanah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Hypertension in adulthood is caused by various risk factors, one of which is stress, so it requires education in controlling changes in blood pressure and stress, it is about 34.1% of productive age have hypertension which has an impact on the risk of cardiovascular disease. Eksoterik is a combination of self-management education and autogenic relaxation exercises. Eksoterik contains education related to control hypertension in the hypertensive adult group in the Curug ward, Depok City. This educational activity aims to improve knowledge and understanding related to control blood pressure and stress in the hypertensive adult group. Education using the EBNP method on 94 hypertensive adults for 12 weeks with meetings once a week. The results of education showed a decline systolic blood pressure started from 142.45 to 133.49 mmHg and diastolic blood pressure from 93.30 to 85.11 mmHg and a decline stress levels started from 24.69 to 17.51. Education shows a positive influence on changes in blood pressure and stress levels in the adult group and raises their awareness to prevent hypertension. Eksoterik based education is also able to strengthen them to practice it independently at home